Pandemic cannot beat us: an interpretative phenomenological analysis of experiences of couples who had to stay apart due to the Covid-19 Pandemic - Gülebakan, Gülşah (İstanbul Bilgi Üniversitesi, 2022)
ABSTRACT: The Covid-19 pandemic brought about many challenges. Due to the restrictions, some geographically close relationship couples had to be physically apart without knowing the duration of restrictions. Some couples had to live their romantic relationships as a long distance relationship. In this study, it was aimed to investigate the experiences of couples who had to stay apart. In Turkey, there is also little research about long distance relationships. Another aim was to contribute the literature about couple relationships. To be able to deeply examine the experiences of couples who had to stay apart due to the pandemic restrictions, a qualitative approach was used. Semi-stractured interviewes were conducted with six heterosexual couples who had to stay apart due to pandemic restrictions and could not meet more than once in a month. After the interviews were done, all interviews were transcribed, analyzed with interpretative phenomenological analysis and four super-ordinate themes emerged: loss of shared environment, adaptation to the new concepts, coping strategies for adaptation to new concepts and in the end. The outcomes showed that despite challenges of separation, adaptation processes and the first reunion after a long separation were difficult to get through; the couples were feeling closer after being able to coping together and seeing the strength of their relationships. The results were discussed in the light of the literature based on long distance relationships, coping strategies for couples in the context of a collective trauma and systemic perspective. Clinical implications and future suggestions were presented.

ÖZET: Covid-19 pandemisi birçok zorluğu da beraberinde getirdi. Kısıtlamalar nedeniyle, coğrafi olarak yakın bazı çiftler, süresini bilmeden fiziksel olarak ayrı kalmışlardır. Bazı çiftler romantik ilişkilerini uzak mesafe ilişkisi gibi yaşamak zorunda kalmışlardır. Bu nedenle bu çalışmada, ayrı kalmak zorunda kalan çiftlerin deneyimlerinin araştırılması amaçlanmıştır. Türkiye'de de uzak mesafeli ilişkiler konusunda çok az araştırma olduğu için çift ilişkileri ile ilgili alan yazına katkı sağlamak bir diğer amaçtır. Pandemi kısıtlamaları nedeniyle ayrı kalmak zorunda kalan çiftlerin deneyimlerini derinlemesine inceleyebilmek için nitel bir yaklaşım kullanılmıştır. Bu çalışmada pandemi kısıtlamaları nedeniyle ayrı kalmak zorunda kalan ve ayda bir defadan fazla görüşemeyen altı heteroseksüel çift ile yarı yapılandırılmış görüşmeler yapılmıştır. Görüşmeler yapıldıktan sonra, tüm görüşmeler yazıya dökülmüş, yorumlayıcı fenomenolojik analiz ile analiz edilmiş ve dört ana tema ortaya çıkmıştır: paylaşılan çevrenin kaybı, yeni kavramlara uyum, yeni kavramlara uyum sağlamak için başa çıkma stratejileri ve sonunda. Sonuçlar, ayrılığın, uyum süreçlerinin ve ilk buluşma anının zorluklarına rağmen, çiftlerin birlikte baş edebildikten ve ilişkilerinin gücünü gördükten sonra birbirlerine karşı daha yakın hissettiklerini göstermiştir. Sonuçlar, uzun mesafeli ilişkiler, kolektif travma bağlamında çiftler için baş etme stratejileri ve sistemik bir bakış açısına dayalı literatür ışığında tartışılmıştır. Klinik uygulamaya yönelik önerilerle birlikte ve gelecek araştırmalar için de öneriler sunulmuştur.
Pandemi bizi yenemez: Covid-19 pandemisi sebebiyle ayrı kalan çiftlerin deneyimlerinin yorumlayıcı fenomenolojik analizi
Keywords: Covid-19 Pandemisi; Fiziken Ayrılmak; Uzak Mesafe İlişkisi; Baş etme Yöntemleri; İlişki Yakınlığı; Covid-19 Pandemic; Physical Separation; Long-Distance Relationship; Coping Strategies; Closeness of Relationship